2019
DOI: 10.1371/journal.pone.0223312
|View full text |Cite
|
Sign up to set email alerts
|

Association between temperature, sunlight hours and alcohol consumption

Abstract: BackgroundAlcohol is a major risk factor for liver cirrhosis. Recently, it was proposed that colder climate might causally lead to increased consumption of alcohol.MethodsWe performed an ecologic study, using monthly updated data on mean temperature, sunlight hours and alcohol consumption from ten regions in Sweden, using publicly available data. A generalised additive model, adjusted for region, was applied to examine the association between mean temperature and mean sunlight hours with mean alcohol consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Additionally, alcohol consumption at high temperatures is an important risk factor for drowning [37,38], as this could affect physiological reactions and behavioral patterns, thereby increasing the risk of drowning. A prior study reported that alcohol consumption was positively correlated with MT [39]. Individuals that consume alcohol have an increased risk of drowning due to greater skin blood flow and sweating.…”
Section: Results Interpretation and Implicationsmentioning
confidence: 94%
“…Additionally, alcohol consumption at high temperatures is an important risk factor for drowning [37,38], as this could affect physiological reactions and behavioral patterns, thereby increasing the risk of drowning. A prior study reported that alcohol consumption was positively correlated with MT [39]. Individuals that consume alcohol have an increased risk of drowning due to greater skin blood flow and sweating.…”
Section: Results Interpretation and Implicationsmentioning
confidence: 94%
“…For the impact of high AT on traumatic fractures, there are some possible explanations. First, high temperature leads to individual negligence, fatigue, and a decline in cognitive function [30][31][32]; Secondly, alcohol consumption increases on days with higher temperatures [33,34]; In addition, the performance of the equipment and road traffic infrastructures are inhibited by high temperature, such as lower driving performance, larger steering adjustments of the vehicle, and loss of signals [35,36]. The above reasons all increase the probability of injuries-related fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of rising temperatures on substance use have not yet been well examined [56]. Higher monthly alcohol consumption during warmer temperature was found in a national Swedish study [57]. A U-shaped association has been observed between apparent temperature (i.e., index combining ambient temperature, humidity, rain, sunshine, and wind) and the incidence of acute excessive drinking in Shenzhen (China; [58]).…”
Section: Rising Average Temperaturesmentioning
confidence: 99%